Die EU-Agrarpolitik und der landwirtschaftliche Strukturwandel in den neuen Bundesländern - Küster, Katrin (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1998)
The structural change of East German agriculture after unification is heavily influenced by the agrarian policy of the EU. But its outcome is not only a product of a rational adaptation to new economic conditions, it also depends on social moments, especially the specific forms of cooperatives in the GDR. So economic considerations, insisting on the advantages of great farms have to be complemented by sociological analysis.